In English Medium Instruction you can walk and chew gum - Han, ZhaoHong (Frontiers in Psychology, 2023)
In English Medium Instruction (EMI), one of the biggest challenges is reportedly the teachers’ own lack of English language proficiency. Helping teachers to improve their proficiency while learning about pedagogy is critical to achieving reasonable success in EMI. This article is contextualized in an English language teacher education program conducted in Tunisia. Specifically, I zoom in on a training task that had trainees reading an academic textbook and posting takeaways on an asynchronous platform over a four-week period. The corpus, comprising 50 journal entries produced by five teacher trainees, was analyzed, first using automated tools for natural language processing and then through human coding, for a combination of quantitative and qualitative perspectives, and with a view to deriving a comprehensive understanding of learning as manifested on multiple levels - psychological, cognitive, and linguistic. Results show impressive learning gains both in content and language. I conclude by discussing the findings and implications for EMI.